Analytical Study To Adjusted Determination Coefficient In A Regression Model - بشماني شكيب (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to describing properties of adjusted determination coefficient , and the cases which takes different values to any regression model , specialist the linear regression, simple or multiple .The important of that is for we know the cases which take minus values which we see them in many researches in high study and in other . We would like to know if these values have a statistical significant or not , and we want to know if they were statistical values , beside of ,we want to explain that with practical examples depending on the relationship between a number of observations and a number of parameters in the model or number of independent variables in the model . The researcher arrived through the study to following results : When coefficient of determination equals 1 the adjusted determination coefficient will equals 1 . When coefficient of determination equals 0 the adjusted determination coefficient will equals a negative value . If the number of parameters bigger than or equal or near of observation number , the adjusted determination coefficient will be unacceptable statistically , because it will bigger than value of determination coefficient . When the number of parameters in the model increase , the value of adjusted determination coefficient will decrease .